Governança corporativa, internacionalização e off-shore companies: o caso Parmalat - Deus, Fagner Oliveira de (2006)
The last five years were marked by the appearance of corporative scandals which have shaken the credibility of the stock market. Situations as those experienced by enterprises such as Enron, Worldcom, Tyco and Parmalat have awaken discussions and have motivated significant changes in the investors and creditors attitude. Besides, they contributed to rekindle the debates related to the theme corporative governance, which aims, among other things, to contribute for ascertaining the return over the investment to those who provide resources for the organizations. Thus, this essay investigates the origin, growing and the ownership and productive structure of Parmalat team, as well as the scandal which involved the enterprise and the consequences, in order to alert investors to the immanent risk of the inobservance in relation to the relevant recommendations of corporative governance. Also, it investigates the case in details, analyzing elements which can raise the development of discussions associated to the theme. This way, a documental, bibliographical research and interviews were used, with which, a triangulation was applied to justify a chronological description of Parmalat case. The events that involved the enterprise are analyzed to the light of the studies of Corporate Governance, whose main themes, in this research were subdivided into three dimensions: a) ownership structure; b) managing practices; and c) public politics. As for results, it was verified that Parmalat investors and creditors had at their disposition clues and evidences of inadequate practices of corporate governance, if observed, would point to a greater risk over the investment rather than the one assumed by the stock agents. Besides, it was observed that the process of internationalization experienced by the enterprise, accelerated and based in acquisitions could have influenced negatively the corporate governance practices. One contribution of this essay was calling the attention to some relationships between corporate governance and off-shore companies, which otherwise, apparently, is still a topic which is not so much studied in the literature.